2000
DOI: 10.1006/viro.2000.0427
|View full text |Cite
|
Sign up to set email alerts
|

Early Alteration of Nucleocytoplasmic Traffic Induced by Some RNA Viruses

Abstract: A HeLa cell line expressing the green fluorescent protein fused to the SV40 T-antigen nuclear localization signal (EGFP-NLS) was established. Fluorescence in these cells was confined to the nuclei. After poliovirus infection, cytoplasmic fluorescence in a proportion of cells could be detected by 1 h postinfection (p.i.) and in virtually all of the fluorescent cells by 2 h p.i. The relocation could be prevented by cycloheximide but not by inhibition of poliovirus replication by guanidine. HCl. Nuclear exit of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
60
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 26 publications
2
60
1
Order By: Relevance
“…For members of the family Picornaviridae, it has been shown that nuclear components, such as Nup153, may be cleaved by the viral 2A pro protein (51). In other cases, classical nuclear import pathways were found to be blocked, resulting in cytoplasmic retention (and accumulation) of nuclear cargo; also, increased diffusion limits by mechanisms that do not depend on caspase activation have been described to be induced in picornavirus-infected cells (51)(52)(53). In contrast to these picornavirus studies, our data suggest transfected with a plasmid that codes either for a GFP trimer that carries a nuclear localization signal (3xGFP) and accumulates in the nucleus or for a GFP pentamer that lacks a nuclear localization signal (5xGFP) and accumulates in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…For members of the family Picornaviridae, it has been shown that nuclear components, such as Nup153, may be cleaved by the viral 2A pro protein (51). In other cases, classical nuclear import pathways were found to be blocked, resulting in cytoplasmic retention (and accumulation) of nuclear cargo; also, increased diffusion limits by mechanisms that do not depend on caspase activation have been described to be induced in picornavirus-infected cells (51)(52)(53). In contrast to these picornavirus studies, our data suggest transfected with a plasmid that codes either for a GFP trimer that carries a nuclear localization signal (3xGFP) and accumulates in the nucleus or for a GFP pentamer that lacks a nuclear localization signal (5xGFP) and accumulates in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…For example, enteroviruses induce a bidirectional increase in permeability of the nuclear envelope accompanied by relocation of some nuclear proteins into the cytoplasm and cytoplasmic ones into the nucleus (8,9). This effect appears to be due to opening of the nuclear pores, as revealed by electron microscopy (10).…”
Section: Discussionmentioning
confidence: 99%
“…Two relevant mechanisms have been described. Poliovirus infection induces an increase in the bidirectional permeability of the nuclear envelope, apparently due to the destruction of nuclear pores, as visualized by electron microscopy (8,10). In addition, active nuclear import via different pathways is also impaired in cells infected with poliovirus and rhinovirus (34,35).…”
mentioning
confidence: 99%
“…In the present study, we investigated the possible role of the cellular protein hnRNP C in the process of PV RNA synthesis. During PV infection, this nuclear RNA-binding protein relocalizes to the cytoplasm due to alterations in nucleocytoplasmic trafficking (9,22,23). Interference with protein trafficking, through the disruption of import and induced efflux of nuclear proteins, may be an essential part of the picornavirus replicative cycle by providing abundant nuclear proteins in the cytoplasm that could function in translation, RNA synthesis, or packaging.…”
Section: Discussionmentioning
confidence: 99%
“…Belov et al have determined that PV infection increases nuclear envelope permeability, resulting in relocalization of nuclear proteins to the cytoplasm, as well as cytoplasmic proteins to the nucleus (9). The findings of Belov et al also indicated that PV-induced permeability does not require caspase-9, a protease that is involved in nuclear permeabilization during apoptosis.…”
mentioning
confidence: 99%